The Paradox of Digital Accountability: A Critical Analysis of Meta’s Ethical Outsourcing in Content Moderation - Alya Salsabila Zahra; Tsabitah Lintang Permata; Desy Dwi Nugrahaini; Adam Farid Hidayat; Pramudya Ibnu Subrata (CITACONOMIA, 2026)
This conceptual article examines the ethical crisis in the global social media ecosystem following Meta's 2025 policy shift, which replaced human fact-checkers with AI-driven Llama automation and